2014
DOI: 10.1002/etc.2625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dissolved organic matter from a eutrophic lake on the freely dissolved concentrations of emerging organic contaminants

Abstract: The authors studied the effects of dissolved organic matter (DOM) on the bioavailability of bisphenol A (BPA) and chloramphenicol by measuring the freely dissolved concentrations of the contaminants in solutions containing DOM that had been isolated from a mesocosm in a eutrophic lake. The abundance and aromaticity of the chromophoric DOM increased over the 25-d mesocosm experiment. The BPA freely dissolved concentration was 72.3% lower and the chloramphenicol freely dissolved concentration was 56.2% lower usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
6
2
Order By: Relevance
“…Most of previous studies suggested the presence of DOM could decrease the freely dissolved HOC concentrations when the total dissolved concentrations of HOCs remain unchanged in water due to the binding of HOCs with DOM, , and, hence, reduce HOC bioavailability and toxicity. For example, Perminova et al found the toxicity of PAHs to Daphnia magna was alleviated by humic acids (HA) and fulvic acids (FA), and Yang et al reported DOM at low levels (3–20 mg C L –1 ) reduced the uptake of cyfluthrin by D. magna . On the contrary, the enhancement of PFAS bioaccumulation by D. magna after addition of DOM at a low level was found by Xia et al because the uptake and elimination rates of PFAS in D. magna were influenced by DOM .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of previous studies suggested the presence of DOM could decrease the freely dissolved HOC concentrations when the total dissolved concentrations of HOCs remain unchanged in water due to the binding of HOCs with DOM, , and, hence, reduce HOC bioavailability and toxicity. For example, Perminova et al found the toxicity of PAHs to Daphnia magna was alleviated by humic acids (HA) and fulvic acids (FA), and Yang et al reported DOM at low levels (3–20 mg C L –1 ) reduced the uptake of cyfluthrin by D. magna . On the contrary, the enhancement of PFAS bioaccumulation by D. magna after addition of DOM at a low level was found by Xia et al because the uptake and elimination rates of PFAS in D. magna were influenced by DOM .…”
Section: Introductionmentioning
confidence: 99%
“…9−12 For example, the distribution, fate, and bioavailability of polycyclic aromatic hydrocarbons (PAHs) are greatly influenced by DOM in natural waters. 13,14 Most of previous studies suggested the presence of DOM could decrease the freely dissolved HOC concentrations when the total dissolved concentrations of HOCs remain unchanged in water due to the binding of HOCs with DOM, 15,16 and, hence, reduce HOC bioavailability and toxicity. 17−19 For example, Perminova et al 20 found the toxicity of PAHs to Daphnia magna was alleviated by humic acids (HA) and fulvic acids (FA), and Yang et al 21 reported DOM at low levels (3− 20 mg C L −1 ) reduced the uptake of cyfluthrin by D. magna.…”
Section: Introductionmentioning
confidence: 99%
“…EP is primarily driven by the UFG-PAA coating solution (55%) and sheet rolling (46%). For the coating solution, both NMP solvent and BPADA are known to directly cause eutrophication in water bodies while the nitrogenous waste released from the upstream production of m- PDA also induces eutrophication . Similarly, cold rolling and the coating solution account for a combined 83% of ODP and 80% of REP.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfonamides (sulfadiazine) and chloramphenicol ( orfenicol) are important classes of most consumed veterinary medicines (Fig. S1) in animal husbandry (Thiele-Bruhn 2003; Xiao et al 2014) and are often reported to interact with DOM in the soil-water system as biologically active compounds (Lou et al 2018;Yang et al 2020;Zhao et al 2019). Understanding the mass ux of these antibiotics and the coupling effects of natural eld environments in association with manure DOM under rainfall conditions is essential to prevent antibiotics pollutions risks and its potential health hazards.…”
Section: Introductionmentioning
confidence: 99%